Light scattering by residual pores in Y₂O₃ nanograined ceramics - Yavetskiy, R.P.; Shpilinskaya, O.L.; Baumer, V.N.; Doroshenko, A.G.; Tolmachev, A.V.; Petrusha, I.A.; Turkevich, V.Z. (Functional Materials, 2013)
Correlation between the in-line optical transmittance and residual porosity of Y₂O₃ nanoceramics formed by high-pressure low-temperature sintering has been established. In the limit case, when the pore diameter is much smaller than the wavelength a formula for estimating the porosity at the known value of linear transmittance was obtained. For investigated samples of nanograin composite ceramics with average grain size of 10–20 nm, the pore size of 12 nm and linear transmittance of 50 % at wavelength of 900 nm the calculated value of residual porosity was 0.27 %. Phase composition of Y₂O₃ nanoceramics may be taken into account by varying refractive index of the composite ceramics containing both cubic and monoclinic yttria.